LEGAL PROTECTION AGAINST FORGERY OF LAND OWNERSHIP HISTORY CERTIFICATES FROM A CRIMINOLOGICAL PERSPECTIVE - Mia Putri Yani, (Proceeding International Conference on Social Sciences, 2026)
The Land Ownership History Certificate (SKRKT) is a fundamental document in Indonesia's land administration system, serving as preliminary proof of ownership prior to the issuance of a certificate. This study aims to analyze the legal protection against SKRKT forgery in Riau from a criminological perspective and the criminological factors that encourage SKRKT forgery based on the Pelalawan District Court Decision Number 285/Pid.B/2021/PN Plw. The researcher used a normative empirical legal research method with a descriptive qualitative approach, such as laws and regulations, court decisions, and legal literature related to the crime of forging land ownership history certificates. This approach was chosen to provide an overview of the legal protection against forgery of land ownership certificates from a criminological perspective. The results of the study show that existing legal protection is not yet fully effective, where law enf orcement is still often hampered and it is difficult to prove the motive and land mafia, especially in cases of forgery in the Pelalawan District Court Decision Number 285/Pid.B/2021/PN Plw. The criminological factor driving this is the economic factor, supported by the weak land administration system at the village/sub-district level and the lack of social control over local authorities. The opportunity factor is dominant because SKRKT is a document that is easy to manipulate. Effective legal protection must be dualistic: (1) Repressive: Strengthening the enforcement of forgery offenses with an emphasis on eradicating organized crime (land mafia), and (2) Criminological Prevention: Total digitization and integration of SKRKT data into the BPN system to minimize opportunities for forgery, as well as increased supervision and integrity of officials authorized to issue initial land ownership documents